Exploring vocabulary teaching: planning and challenges with the implementation of audio-visual approach in rural East Malaysian primary-level English language classrooms - Lim, Bryan Chen Yang; Joseph Ramanair; Soo, Ruey Shing (Penerbit Universiti Kebangsaan Malaysia, 2023)
Vocabulary is key to effective communication. Previous studies revealed that teachers often overlook vocabulary teaching compared to other language skills such as speaking, listening, grammar, reading, and writing. The integration of technology into the Malaysian education system has raised concerns about how vocabulary lessons are planned and executed in English classrooms, particularly in rural Sarawak schools in Malaysia. Studies in the past found that teachers have been hesitant to use Common European Framework of Reference for Languages (CEFR) aligned resources despite knowing about their availability. This research was conducted to determine the teachers' vocabulary lesson planning and the challenges teachers experienced when using the audio-visual (AV) approach to teach vocabulary in the primary-level English language classroom. Based on the purposive sampling technique, three primary-level English language teachers from one school in a rural area of Bau, Sarawak, participated in this study to provide rich information relevant to the research questions. Data were collected through semi-structured interviews, classroom observation and document analysis, and were analysed thematically based on Braun and Clarke's (2006) thematic analysis method. The findings indicated that teachers referred to CEFR-aligned documents for lesson planning especially when selecting resources and using the framework as a benchmark for practice. The findings indicated that teachers were facing challenges in two primary areas: infrastructure challenges related to information technology and policy challenges related to the CEFR. The results from this study provide practitioners with practical insights into how rural teachers implement the AV approach to teaching vocabulary in their classrooms.